Separation of Isomeric Tau Phosphopeptides from Alzheimer's Disease Brain by Cyclic Ion Mobility Mass Spectrometry - Kováč, Andrej; Majerová, Petra; Nytka, Marianna; Cechová, Monika Zajacová; Bednář, Petr; Hájek, Roman; Cooper-Shepherd, Dale A; Muck, Alexander; Lemr, Karel (Journal of the American Society for Mass Spectrometry, 2023)
Alzheimer's disease (AD) is a neurodegenerative disorder of increasing concern. It belongs to diseases termed tauopathies which are characterized by inclusions of abnormally hyperphosphorylated and truncated forms of the protein tau. Studies of tauopathies often focus on detection and characterization of these aberrant tau proteoforms, in particular the phosphorylation sites, which represent a significant analytical challenge for example when several phosphosites can be present on the same peptide. Such isomers can even be difficult to fully separate chromatographically. Since recently introduced cyclic ion mobility-mass spectrometry can offer different selectivity, we have investigated the closely positioned phosphorylation sites S214, T212, and T217 of a tryptic peptide from proline rich region of tau-TPSLPTPPTREPK. The conformational heterogeneity of the isomeric peptides in the gas phase hindered their separation due to their overlapping arrival time distributions. Increasing the resolution of the analysis alone is insufficient to distinguish the peptides in a mixture typical of patient samples. We therefore developed a method based on a combination of collision-induced dissociation, isomeric product ions (m/z 677) mobility separation and post-mobility dissociation to aid in analyzing the isomeric phosphopeptides of tau in diseased brain extract. For all three isomers (T212, S214, and T217), the ion mobility signal of the ion at m/z 677 was still observable at the concentration of 0.1 nmol/L. This work not only offers insights into the phosphorylation of tau protein in AD but also provides an analytical workflow for the characterization of challenging pathological protein modifications in neurodegenerative diseases.
Keywords: proteiny tau; Brain; Phosphopeptides; tau Proteins; mozek; Humans; lidé; Alzheimer Disease; hmotnostní spektrometrie; fosfopeptidy; Alzheimerova nemoc; Mass Spectrometry